Pelanggaran Warga Negara Asing Di Indonesia Ditinjau Dari Hukum Internasional - Amara Nur Nabila; Intan Handayani; Yodha Bandung Wiradhika; Nauval Bagus Satria; Dewi Rahmawati Gustini (Peneliti.net, 2023)
As a state of independence and sovereignty, Indonesia has a legal basis for making government policies, the 1945 Constitution of the Republic of Indonesia, which is the basis for making policies and various laws in Indonesia, including laws for violations committed by foreign nationals. In its implementation, international law provides the right and authority to regulate all legal events in the territory of its country, this is done because each country has different needs in each country. Immigration is about the traffic of people entering or leaving the territory of Indonesia and its supervision in order to maintain the sovereignty of the state. Deportation cannot be done carelessly, there must be reasons such as endangering the country and disturbing order and harming the country. The state cannot deport because foreign nationals have the rights to protection enshrined in the Declaration of Human Rights, so it must follow the provisions set by state law and international law.